Discharge coefficient of high viscosity liquids through nozzles - Essien, S.; Archibong-Eso, Archibong; Lao, Liyun (Elsevier, 2019)
Experimental investigation on discharge coefficient, Cd, for high viscosity fluid through nozzles was carried out. The viscosity of the fluid used for the test ranged from 350 to 1500 mPa s. The length-to-diameter ratio of the nozzle, l/d and the ratio of nozzle diameter to pipe diameter ratios β were used to investigate the influence of geometry on Cd. Results show a significant dependence of Cd on Re, l/d and β ratio. An empirical correlation on the discharge coefficient was developed based on the data from this study which was also compared with data from other published studies. This correlation, with an R-squared value of 0.9541, was valid for nozzle sizes 10–20 mm and for Re between 1 and 200. Cd values obtained from experimental data, and those from the empirical correlation were compared, and a mean standard deviation of 0.0231 was obtained.
Keywords: discharge coefficient; Reynolds number; length-to-diameter ratio; beta ratio; viscosity